Textual Transcendence in the Stories of “The Dark and the Bright” by Dr. Iman Al-Sultani - Mohammed, Lecture Maha Hilal (Thi Qar Arts Journal, 2024)
The research addresses the issue of textual transcendence or textual thresholds or the parallel text in the stories of “The Dark and the Bright” by Dr. Iman Al-Sultani, which are published by Al-Najaf Al-Ashraf Creativity Publications for the year 2008. It includes a theoretical introduction followed by an analysis of the cover art, succeeded by a second reading (interpretative of the main title) and then the internal titles of the stories, taking into account their syntactic (grammatical) level, along with a summary for each story; so that the esteemed reader can grasp the proceedings of the internal content, concluding the research journey with a study of the link between the titling and the read text (the story).